The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1361-6528/ab7fcc
|View full text |Cite
|
Sign up to set email alerts
|

Synergy effect in hybrid nanocomposites based on carbon nanotubes and graphene nanoplatelets

Abstract: Hybrid nanocomposites reinforced with a mixture of graphene nanoplatelets (GNPs) and carbon nanotubes (CNTs) have shown improvement in filler dispersion while providing a cost-effective alternative to CNT monofiller composites. Depending on their composition, hybrid composites can exhibit electrical performance superior to either of the constituent monofiller composites due to synergistic effects. In this work, we develop a three-dimensional tunneling-based continuum percolation model for hybrid nanocomposites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…For polymer matrix reinforced with microscale fibers; such as carbon fibers (CF) and fiberglass, an infinite aspect ratio is commonly used for the fiber unless it is chopped. However, for the nanoscale fillers or particles, such as graphene nanoplatelets and carbon nanotubes, the situation is different as these nanofillers are produced with a wide range of aspect ratios [39][40][41][42]. The reported results from experiments that have been conducted to capture the influence for particular carbon nanofiller sizes (aspect ratio) mostly refer to an improvement in the engineering properties of nanocomposites as the aspect ratio increases [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For polymer matrix reinforced with microscale fibers; such as carbon fibers (CF) and fiberglass, an infinite aspect ratio is commonly used for the fiber unless it is chopped. However, for the nanoscale fillers or particles, such as graphene nanoplatelets and carbon nanotubes, the situation is different as these nanofillers are produced with a wide range of aspect ratios [39][40][41][42]. The reported results from experiments that have been conducted to capture the influence for particular carbon nanofiller sizes (aspect ratio) mostly refer to an improvement in the engineering properties of nanocomposites as the aspect ratio increases [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the nanoscale fillers or particles, such as graphene nanoplatelets and carbon nanotubes, the situation is different as these nanofillers are produced with a wide range of aspect ratios [39][40][41][42]. The reported results from experiments that have been conducted to capture the influence for particular carbon nanofiller sizes (aspect ratio) mostly refer to an improvement in the engineering properties of nanocomposites as the aspect ratio increases [41][42][43][44]. Unfortunately, experimental techniques are infeasible and limited to investigating the role of aspect ratio in reinforcing polymer matrix with nanoscale fillers.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the possibility of combining graphene and CNTs has attracted much attention from the research community in order to obtain new multifunctional hybrid materials with promising properties due to the synergistic effect caused by the interaction of nanostructures of various dimensions—1D nanotubes and 2D graphene [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. In addition, hybridization of graphene and CNTs will make it possible to avoid the agglomeration of individual CNTs and graphene sheets, which leads to a significant deterioration in the properties of the aforementioned carbon nanomaterials in a real experiment.…”
Section: Introductionmentioning
confidence: 99%
“…He studied the mergers and acquisitions of companies in various industries during the years, and finally concluded that the positive wealth effect obtained by mergers and acquisitions comes from the synergy effect. Since financial indicators have made up for the shortcomings of the capital market to a certain extent, scholars have been currently using this method for analysis [ 17 21 ]. Sarala R M et al compared the four accounting indicators before and after the reorganization of the company.…”
Section: Introductionmentioning
confidence: 99%